MITIGASI KONFLIK GAJAH-MANUSIA PASCA BENCANA HIDROMETEOROLOGI DI KABUPATEN ACEH TENGAH - Sutrisno Sutrisno; Halisasimi Halisasimi (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2026)
This study aims to analyze the characteristics and driving factors of post-disaster human-elephant conflict and to formulate mitigation strategies integrated with Disaster Risk Reduction (DRR). Employing a qualitative approach with an exploratory case study design, the research was conducted in Karang Ampar Village, Central Aceh Regency, an area that experienced severe isolation following the impact of Tropical Cyclone Senyar in November 2025. Data were collected through field observations, in-depth interviews with affected communities and key stakeholders, and supporting documentation, and were analyzed using Miles and Huberman's interactive analysis model. The findings indicate that the intensification of post-disaster human-elephant conflict is driven by four main factors: habitat degradation and scarcity of natural forage, alterations in elephant migration corridors, damage to conflict mitigation infrastructure, and increased socio-economic vulnerability of local communities following the disaster. Hydrometeorological disasters function as trigger events that accelerate shifts in elephant movement patterns toward human settlements, while simultaneously reducing community capacity to respond to conflict in a safe and adaptive manner. This study recommends an integrated mitigation strategy encompassing habitat rehabilitation through Nature-based Solutions, strengthening disaster-resilient mitigation infrastructure, community empowerment based on conservation and disaster resilience, and the reinforcement of institutional and spatial policy frameworks. Such an integrated approach is essential not only to reduce the intensity of human-elephant conflict but also to enhance post-disaster socio-ecological resilience in Central Aceh.